PENGARUH ENTREPRENEURSHIP EDUCATION DAN INNOVATION CAPABILITY TERHADAP ENTREPRENEURIAL INTENTION DENGAN SELF EFFICACY SEBAGAI VARIABEL MEDIASI - Eka Adhitya Yuana Putra; Sidiq Permono Nugroho (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
This research was conducted to examine the effect of entrepreneurship education and innovation capability on entrepreneurial intention with self-efficacy as a mediating variable. The sample in this study were active students who took the Management study program in Surakarta using a random sampling technique. Collecting data using a questionnaire to 150 respondents. The data analysis tool in this study used smart PLS version 3.2.8, with testing the outer model and inner model. The results of this study indicate that (1) entrepreneurship education has a negative effect on entrepreneurial intention. (2) entrepreneurship education has a positive effect on self-efficacy. (3) innovation capability has a positive effect on entrepreneurial intention. (4) innovation capability has a positive effect on self-efficacy. (5) self-efficacy has a positive effect on entrepreneurial intention. (6) entrepreneurship education has a positive effect on entrepreneurial intention mediated by self-efficacy. (7) innovation capability has a positive effect on entrepreneurial intention mediated by self-efficacy.